An Analytical Study of Kitab Kuning Learning Methods at Darul Hikmah Pasundan Islamic Boarding School, Sukanegara, Central Lampung - Rinto Ariyanto; Imam Roiz Zalaluddin (Episteme: Jurnal Kajian Mahasiswa, 2025)
Islamic boarding schools are traditional educational institutions that play a very important role in the general public, so Islamic boarding schools must be able and must be able to keep up with the times. Therefore, Islamic boarding schools must develop their learning methods in order to improve the quality of more quality, effective and innovative knowledge interpretation The most basic problem in understanding the Yellow Book is related to the mastery of the Arabic language, because all the reading literature is in Arabic. In the tradition of pesantren, the curriculum that is the basis for mastering Arabic must have at least two, namely nahwu and sharaf. These two basic sciences are the entrance gate to understand and study the various yellow books. This study aims to describe and analyze the learning method of the yellow book in Pon-Pes Darul Hikmah Pasundan Sukanegara. The formulation of the problem in this study is how the learning method of the yellow book in Pon-Pes Darul Hikmah Pasundan Sukanegara, Bangunrejo District, Central Lampung Regency. This study uses a qualitative approach that contains an explanation of the data obtained in the field. There are three data collection techniques used in this study, namely interviews, observations, and documentation. The data obtained is then analyzed by reducing the data, presenting the data, and drawing conclusions. The results of the research conducted show that 1) The book studied at Pon-Pes Darul Hikmah Pasundan still uses the classical books of previous scholars, Syekh Salim Bin Sumer Al-Hadromi, Imam Ghozali, Syekh Mahmud Bin Mukhtar Cirebon. so that its authenticity and authenticity are still maintained. 2) the learning method of the yellow book in pon-pes darul hikmah pasundan is divided into 3, namely the bandongan method, the sorogan method, and komprehensif. 3) the lack of human resources (HR) does not affect the learning activities of students in studying the Yellow Book, in the process of teaching and learning activities, every week an evaluation meeting is held between teachers to follow up in terms of shortcomings in teaching or methods used.